2003
DOI: 10.1046/j.1365-2273.2003.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of expiration on particle deposition within the nasal cavity

Abstract: One of the most important functions of the nose is cleansing the inspired air. The aim of this study was to compare the intranasal deposition of particles during inspiration and expiration, applying different breathing manoeuvres. In nine subjects, the non-deposited particles during inhalation of an aerosol of starch particles were laser-optically detected by placing a suction probe transnasally in the anterior nasal segment. The particle deposition was measured during cyclical nose-in/nose-out (nose-only) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Preliminary results from in vivo and in vitro methods have confirmed the individual differences in nasal anatomy which leads to intersubject variability in aerosol deposition (Bennett & Zeman, 2005;K.-H. Cheng et al, 1996;Cheng et al, 1991Cheng et al, , 1995Y. S. Cheng et al, 1996;Cheng, 2003;Garcia, Tewksbury, et al, 2009;Kesavan et al, 2000;Kesavanathan & Swift, 1998;Kesavanathan, Bascom et al, 1998;Rasmussen et al, 2000;Wiesmiller et al, 2003). Recently, investigations using CF-PD modeling methodology also predicted subject variability in nasal deposition (Dastan et al, 2014;Garcia, Schroeter, et al, 2009;Keeler et al, 2016;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 85%
“…Preliminary results from in vivo and in vitro methods have confirmed the individual differences in nasal anatomy which leads to intersubject variability in aerosol deposition (Bennett & Zeman, 2005;K.-H. Cheng et al, 1996;Cheng et al, 1991Cheng et al, , 1995Y. S. Cheng et al, 1996;Cheng, 2003;Garcia, Tewksbury, et al, 2009;Kesavan et al, 2000;Kesavanathan & Swift, 1998;Kesavanathan, Bascom et al, 1998;Rasmussen et al, 2000;Wiesmiller et al, 2003). Recently, investigations using CF-PD modeling methodology also predicted subject variability in nasal deposition (Dastan et al, 2014;Garcia, Schroeter, et al, 2009;Keeler et al, 2016;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 85%
“…For example as shown by Pattle (1961), the inspiratory nasal deposition efficiency for a subject is a unique function of IP, i.e., where is the deposition efficiency and a is a correlation coefficient. Wiesmiller et al (2003) investigated the impact of expiration on particle deposition within the nasal cavity in nine subjects with particle sizes ranging from 1 to 30 m. It was found that nasal particle deposition takes place mainly during inspiration and to a much lower degree during expiration. Kesavanathan, Bascom, and Swift (1998) studied the effect of nasal passage characteristics on particle deposition with polydispersed (1.10 m) aerosols drawn unidirectionally (Q = 30 L/min) into the nose and out of the mouth for 40 subjects.…”
Section: Inertial Particle Depositionmentioning
confidence: 99%
“…51 Sivasankar and Fisher 52 report the adverse effects of short-term oral breathing and suggest a possible link that oral breathing may predispose people to vocal pathology. Nose breathing is recommended for voice use rather than mouth breathing.…”
Section: Breathing Through My Nosementioning
confidence: 99%